PENGARUH KOMPENSASI, PENGEMBANGAN KARIR TERHADAP KOMITMEN ORGANISASI KARYAWAN PADA PT. SIANTAR TOP TANJUNG MORAWA - Muhammad Ayyub; Amirudin, Mella Yunita (CV. ADIBA AISHA AMIRA, 2025)
The purpose of this study was to determine the effect of compensation and career development on organizational commitment at PT. Siantar Top Tanjung Morawa. The population and sample of this study were 85 employees of PT. Siantar Top Tanjung Morawa. The research tool used was a Likert scale model questionnaire. The data analysis method used was multiple regression analysis with a significance level of a = 0.05. The results of this study indicate that the calculated t is greater than the t table (3.871285 ̃ 1.66365) and a significance value of 0.0002, the results of the study indicate that compensation (X1) has a significant effect on employee organizational commitment at PT. Siantar Top Tanjung Morawa. At PT. Siantar Top Tanjung Morawa, career development (X2) has a significant effect on employee organizational commitment, as evidenced by the calculated t value greater than the t table (3.680123> 1.66365) with a significance value of 0.0002. Based on the E-Views 10 output, it is known that the large contribution of independent variables to the explanation of related variables is indicated by the R square value of 0.333246 or 33.32%. As much as 33.32% of organizational commitment at PT. Siantar Top is attributed to compensation and career development, while the remaining 66.68% are other variables